Computational analysis of the enantioselectivity of diels-alder reactions involving chiral cationic oxazaborolidinium catalyst / Nasr Y.M. Omar - Nasr, Y. M. O. (2011)
This thesis is divided into six chapters. In the first chapter, the results of standard high-performance computing (HPC) benchmarks are presented in order to assess the performance characteristics of the various hardware and software components of an own built commodity-class Linux cluster. Introductions to enantioselective synthesis and quantum mechanical methods are provided in the second chapter. The third chapter gives insights into the enantioselectivity and mechanism of the organocatalytic Diels-Alder reaction using density functional theory (DFT) at the B3LYP/6-31G(d) level of theory. The fourth chapter attempts to rationalize the enantioselectivity and mechanism of the organocatalytic Diels-Alder reaction using various aspects of DFT. The organocatalytic solid-phase Diels-Alder reaction in terms of enantioselectivity and mechanism is theoretically investigated in the fifth chapter using the hybrid method ONIOM(QM:MM). The sixth chapter deals with the same organocatalyst but as applied to cyanosilylation of aldehydes. The mechanism and enantioselectivity of this reaction are also investigated by means of DFT at the B3LYP/6-31G(d) level of theory.